Disparity in the micronutrient content of diets high or low in advanced glycation end products (AGEs) does not explain changes in insulin sensitivity. (17th November 2017) - Pearce, Karma; Hatzinikolas, Alicia; Moran, Lisa; de Courten, Maximilian P. J.; Forbes, Josephine; Scheijen, Jean L. J. M.; Schalkwijk, Casper G.; Walker, Karen; de Courten, Barbora
Abstract: We have previously shown that an isoenergetic low advanced glycation end products (AGEs) diet matched for macronutrient content improved insulin sensitivity compared to high AGE diet. Here, we evaluated the differences in micronutrient intake of these two dietary patterns and if they could explain differences in insulin sensitivity. Participants consumed the intervention diets each for 2 weeks with 4 weeks of habitual dietary intake (washout) in-between. Dietary analysis revealed that the high AGE diet contained greater levels of retinol equivalents (RE) (478.9 + 151.3 μg/day versus 329.0 + 170.0 μg/day; p < .006), vitamin A (806.3 + 223.5 (μg RE)/day versus 649.1 + 235.8 (μg RE)/day; p < .05) and thiamine (2.3 + 0.6 mg/day versus 1.6 + 0.4 mg/day; p = .014) compared to the low AGE diet. The changes in polyunsaturated fat, retinol, vitamin A and thiamine did not correlate with changes in insulin sensitivity (all p > .1) therefore are unlikely to explain observed changes in insulin sensitivity. (clinicaltrials.gov:NCT00422253).